Balanced Nutrition Education and Early Detection of Chronic Energy Deficiency among Adolescents at Muhammadiyah 2 Junior High School, Ternate City - Agustin Rahayu; Diah Merdekawati Surasno; Suryani Mansyur; Andiani; Tati Sumiati; Nani Supriyatni; Yusnita; Suryadi M. Ali; Sitti Nurhidayanti Ishak; Musiana; Monisa A. Hi. Djafar; Mayasari Soamole (BIOSAINSTEK, 2026)
Adolescents are vulnerable to nutritional problems due to increased nutritional requirements during rapid growth and development. One of the common nutritional problems among adolescent girls is Chronic Energy Deficiency (CED), which may affect their future health and reproductive function. This community service activity aimed to improve students’ knowledge about balanced nutrition and conduct early detection of nutritional risk, particularly CED, among students of Muhammadiyah 2 Junior High School, Ternate City. The activity was conducted on November 8, 2025, involving 31 students from grades VII, VIII, and IX. The methods included balanced nutrition education through lectures and interactive discussions, followed by nutritional status screening using anthropometric measurements, including body weight, height, and Mid-Upper Arm Circumference (MUAC) among female students. Knowledge improvement was assessed using pre-test and post-test questionnaires and analyzed using the paired t-test. The results showed an increase in the mean knowledge score from 7.10 before the intervention to 8.48 after the intervention, with a mean difference of 1.387 and a statistically significant difference (p = 0.002). Anthropometric assessment showed that the average MUAC among female students was 22.08 cm, with 5 students (38.5%) identified as being at risk of CED based on MUAC measurements. Conclusion, balanced nutrition education effectively improved students’ knowledge, and nutritional screening is important for early identification of nutritional risks. Routine nutritional monitoring in schools is recommended to support adolescent health and prevent future nutritional problems.